2019
DOI: 10.3389/fimmu.2019.02950
|View full text |Cite
|
Sign up to set email alerts
|

The Skin and Intestinal Microbiota and Their Specific Innate Immune Systems

Abstract: The skin and intestine are active organs of the immune system that are constantly exposed to the outside environment. They support diverse microbiota, both commensal and pathogenic, which encompass bacteria, viruses, fungi, and parasites. The skin and intestine must maintain homeostasis with the diversity of commensal organisms present on epithelial surfaces. Here we review the current literature pertaining to epithelial barrier formation, microbial composition, and the complex regulatory mechanisms governing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 120 publications
0
63
0
Order By: Relevance
“…The identification of factors predicting immune-related toxicity is a current need and preclinical and clinical studies have highlighted the impact of the gut microbiota on irAEs [ 28 , 40 ]. The gut microbiota has been proved to be a major regulator affecting skin homeostasis, likely through mechanisms related to the modulatory effects that the gut microbial community exerts on systemic immunity or via metabolite products, such as phenols that access circulation and get the distant skin [ 55 , 56 ]. In the present research, we have highlighted a decrease of the gut microbiota diversity in patients with skin toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of factors predicting immune-related toxicity is a current need and preclinical and clinical studies have highlighted the impact of the gut microbiota on irAEs [ 28 , 40 ]. The gut microbiota has been proved to be a major regulator affecting skin homeostasis, likely through mechanisms related to the modulatory effects that the gut microbial community exerts on systemic immunity or via metabolite products, such as phenols that access circulation and get the distant skin [ 55 , 56 ]. In the present research, we have highlighted a decrease of the gut microbiota diversity in patients with skin toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Skin commensal bacteria have a close relationship with host immune cells from the beginning of their life, and skin resident T cells are thus trained to respond to potential transitory pathogenic bacteria [ 20 , 31 ]. Meisel et al [ 23 ] showed that the expression of 2820 genes was modulated in mice in response to microbial colonization.…”
Section: Role Of the Skin Microbiomementioning
confidence: 99%
“…The toxins produced by S. aureus interact with the immune system: α-toxin induces IL-1β production from monocytes, which can promote a T helper 17 (Th17) response or cytokine IL-17 production from CD4+ T cells; δ-toxin induces mast cell degranulation ( Figure 2 ). Murine models have demonstrated that S. aureus triggers adipocyte proliferation and stimulates the production of higher amounts of antimicrobial peptides, such as cathelicidin; strains belonging to this species also induce skin immune cells to produce cytokines IL-4, IL-13, and IL-22, as well as stromal lymphopoietin; these abnormal conditions seem to be responsible for alterations in the epithelial barrier [ 72 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Atopic Eczema/dermatitis Syndrome and Skin Microbiotamentioning
confidence: 99%